Frequency and Clinical Manifestations of Papilloma Viral Infection of a High Oncogenic Risk in Men of Family Couples - Rafikovna, Khakimova Leyla (European Journal of Life Safety and Stability (2660-9630), 2022)
This article summarizes a study of 38 couples who continued uninterrupted sexual life for at least 3 years, in which partners were carriers of oncogenic types of HPV. DNA of oncogenic HPV strains in the studied samples was detected by real-time PCR. Work consisted in determining the frequency of infection and describing the clinical manifestations of PVI in men from married couples with an infected partner.